BEAM: branch-based efficient and adaptive multicast for wireless sensor networks. (2017) - Kim, Daehee; Song, Sejun; Choi, Baek-Young
Multicast has been largely used for one-to-many distribution in wireless sensor networks (WSNs). However, existing multicast protocols have various overhead issues such as large forwarding states, control messages, packet header sizes, computation time, and energy consumption. In this paper, we propose a resilient and efficient branch-based multicast protocol, branch-based efficient and adaptive multicast for wireless sensor networks (BEAM) that reduces forwarding states and control messages by building efficient multicast paths on-demand using branch-based membership establishment, and that efficiently decreases packet header and computation overhead using branch-based data forwarding. Furthermore, for long-lived WSNs, BEAM resiliently keeps maintaining efficient multicast path with low overhead on continuous membership establishments based on quality of branches. Extensive evaluation results show that BEAM has less overhead complexity, packet overhead by 40%, and energy consumption by 30% than existing stateless multicast protocols.